La marginalidad en el Pastor de Hermas - Álvarez Cineira, David (Cauriensia, 2022)
The metropolis of Rome offers in the second century A.C. many opportunities to Christian brokers looking to enrich themselves with their businesses. However, the excessive preoccupation with the commercial success leads to the diluted identity and community commitment of rich Christians. Faced with this possible loss of identity, Hermas, previously a broker, urges his former colleagues to reduce their business efforts and direct the productive surplus of their businesses towards the care of the Christian poor and widows in order to enhance their community involvement while offering them an identity marginality thanks to the creation of a "virtual citizenship".